2004
DOI: 10.1139/x03-269
|View full text |Cite
|
Sign up to set email alerts
|

Spruce budworm outbreaks in eastern Quebec over the last 450 years

Abstract: In this study we used dendrochronology to reconstruct the history of eastern spruce budworm (Choristoneura fumiferana (Clem.)) outbreaks over the last 450 years in the Bas-Saint-Laurent region of southeastern Quebec. In total, 260 tree cores were sampled from 204 beams in seven historic buildings and 12 trees in a virgin forest stand. Eight previously documented outbreaks (1975–1992, 1947–1958, 1914–1923, 1868–1882, 1832–1845, 1805–1812, 1752–1776, 1710–1724) and three presumed previous outbreaks (1678–1690, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
150
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(162 citation statements)
references
References 23 publications
9
150
1
2
Order By: Relevance
“…4) that correspond to the four classes of defoliation impact proposed by Gray et al [14]. For a period of 30 years, a time roughly equivalent to the return interval of the recent spruce budworm outbreak [9], these volume losses were estimated at 2, 8, 15 and 24% for the negligible, light, moderate, and severe classes of defoliation impact, respectively. Similar results have been derived from a process-based model developed by Baskerville and Kleinschmidt [3] for balsam fir stands subjected to defoliation by spruce budworm in north-central Maine and New Brunswick.…”
Section: Growth Lossesmentioning
confidence: 99%
See 1 more Smart Citation
“…4) that correspond to the four classes of defoliation impact proposed by Gray et al [14]. For a period of 30 years, a time roughly equivalent to the return interval of the recent spruce budworm outbreak [9], these volume losses were estimated at 2, 8, 15 and 24% for the negligible, light, moderate, and severe classes of defoliation impact, respectively. Similar results have been derived from a process-based model developed by Baskerville and Kleinschmidt [3] for balsam fir stands subjected to defoliation by spruce budworm in north-central Maine and New Brunswick.…”
Section: Growth Lossesmentioning
confidence: 99%
“…B.S.P.). A recent historical study based on tree-ring analyses have shown that the frequency of spruce budworm outbreaks has remained quite stable over the last four centuries [9], presumably because of the continuous abundance of balsam fir stands [8,24,25]. Since fir-dominated stands are still abundant and are expected to remain so into the future, sustained management of these forests must consider the impact of future insect defoliation by integrating estimation of wood losses in volume prediction models.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the conifer forests of northern North America, Nosema fumiferanae is a microsporidium that is considered a regulating component of outbreaks of the eastern spruce budworm, Choristoneura fumiferana (Régnière 1984;van Frankenhuyzen et al 2007). Extensive defoliating outbreaks of this moth occur in 35-40 year cycles (Royama 1984;Boulanger & Arseneault 2004), in which N. fumiferanae and other entomopathogens and parasites increase and decrease with host density and can dampen the outbreaks (Eveleigh et al 2007). In the extended periods between budworm outbreaks, N. fumiferanae maintains infection across seasonal generations via transovarial transmission (Eveleigh et al 2012).…”
Section: Gypsy Moth: Nosema Lymantriae and Vairimorpha Disparismentioning
confidence: 99%
“…The natural disturbance regime was characterized by recurring spruce budworm (Choristoneura fumiferana (Clem.)) outbreaks, which can lead to small or major disturbances [27]. The site was part of the Fir-Yellow Birch (Betula alleghaniensis Britt.)…”
Section: Study Sitementioning
confidence: 99%